Find ∫ x = 0 ∞ d x ∫ y = 0 1 d y ∫ z = 0 x d z x e ( − 2 y x − 3 x y − 5 y z ) = K .
Enter your answer as K 1
Bonus: Try generalise
∫ x = 0 ∞ d x ∫ y = 0 1 d y ∫ z = 0 x d z x e ( − A y x − B x y − C y z )
For positive A,B and C.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Here is another way of doing it!!
Once we have done the z integral, then we are left with integrals of the form
∫ x = 0 ∞ ∫ y = 0 1 c y − x exp ( − ( A y x + B x y ) ) d y d x
Knowing that the order of integration can be changed, thus
∫ 0 ∞ x exp ( − A x ) d x = A 2 1 So, we are left with
∫ 0 1 ( B y 2 + A ) 2 y d y = 2 A ( A + B ) 1 So,
∫ x = 0 ∞ ∫ y = 0 1 ∫ z = 0 x x exp ( − ( A y x + B x y + C y z ) ) d z d y d x = 2 A ( A + B ) ( A + B + C ) 1